Oceanographic connectivity and environmental correlates of genetic structuring in Atlantic herring in the Baltic Sea. (4th February 2013) - Teacher, Amber GF; André, Carl; Jonsson, Per R; Merilä, Juha
Abstract Marine fish often show little genetic structuring in neutral marker genes, and Atlantic herring (Clupea harengus) in the Baltic Sea are no exception; historically, very low levels of population differentiation (FST ≈ 0.002) have been found, despite a high degree of interpopulation environmental heterogeneity in salinity and temperature. Recent exome sequencing and SNP studies have however shown that many loci are under selection in this system. Here, we combined population genetic analyses of a large number of transcriptome‐derived microsatellite markers with oceanographic modelling to investigate genetic differentiation and connectivity in Atlantic herring at a relatively fine scale within the Baltic Sea. We found evidence for weak but robust and significant genetic structuring (FST = 0.008) explainable by oceanographic connectivity. Genetic differentiation was also associated with site differences in temperature and salinity, with the result driven by the locus Her14 which appears to be under directional selection (FST = 0.08). The results show that Baltic herring are genetically structured within the Baltic Sea, and highlight the role of oceanography and environmental factors in explaining this structuring. The results also have implications for the management of herring fisheries, the most economically important fishery in the Baltic Sea, suggesting that the current fisheries management units may be in need of revision.